Assessing the conservation status of the Sinai Baton Blue butterfly (Pseudophilotes sinaicus) - Thompson, Katy (2013)
Arid environments are resource-limited, with scarcity of water the key limiting factor for plants and their associated fauna. Consequentially bottom-up forces often control food webs, influencing the whole system through high levels of competition. The Sinai Baton Blue butterfly, Pseudophilotes sinaicus, is Critically Endangered, with a tiny endemic distribution in the St Katherine Protectorate, South Sinai, an arid environment. Its range is restricted to that of its sole host plant, the near-endemic endangered Sinai Thyme, Thymus decussatus, leaving the butterfly in a highly fragmented distribution. This study looks into the spatio-temporal variations in quality and abundance of the host plant and its implications for the Sinai Baton Blue. Over the past decade the butterfly has exhibited severe population cycles, with the causes still unclear; it could be due to the fluctuating resource levels with large temporal variation in the quality of thyme and density of inflorescences. The number of flowers significantly influences the larval distribution, indicating that resources play a key role in offspring survivorship. Population viability analysis has also highlighted the importance of management techniques aimed at increasing the butterfly's survivorship. The butterfly population sizes are positively correlated with the total resource area and the number of host plants but not the distance between habitat patches. Population viability analysis also suggests that habitat area is more influential than connectivity in this system driving current dynamics. Overall this project has highlighted the urgent need for conservation focused on improving plant quality within patches in order to save this fragile species.